A study on effectiveness of child-centered and play-based home support education program on children who have development problems [Gelişimsel sorunları olan çocuklarda oyun temelli ev ve çocuk merkezli eğitim programının etkililiği üzerine çalışma] - (:unkn) unknown (Hacettepe University, 2017)
This study was conducted with four participants at high risk for autism, who consulted a psychiatrist independent of the study, due to their families noticing developmental abnormalities. This study presents four months, six months, two years - three months and one year - ten months durations based results of the four participants of the play-based home support educational program respectively. Semi-experimental research methods with a single group pretest-posttest model were used in this study. It was observed that the application of a play-based home support and child-centered educational programs to four children of different ages demonstrated strong symptoms of autism resulted in improvements in all sub-scales of ADSI(AGTE), with greater developments specifically in the linguistic-cognitive scale. Results of the ABC, despite the fact that the educational program was administered to each child for different lengths of time; indicated an observable decline in autism symptoms in all sub-areas. © 2017, Hacettepe University. All rights reserved.
Keywords: Home support; Play-based education; Special education